Return to Literature. A Manifesto in Favour of Theory and against Methodologically Reactionary Studies (Cultural Studies etc.) (Comparatismi, 2018)
What is literature for us today? And what will become of it in the next few years? Our era only seems willing to recognize the complexity of the field of science; whereas as far as literature is concerned, it is still thought that a rigorous training is not necessary and many deceive themselves into thinking that it is possible to do without the analytical tools created in the twentieth century and more recently thanks to theory.The refusal of theory is justified by the most tenacious prejudices, or simply by bad faith. It is believed (or some pretend to believe) that literary theory coincides with the years of structuralism, with the primacy of linguistics, and with the thesis of the intransitivity of language.Reality is quite different. Literary theory is a hybrid space where linguistics, rhetoric, philosophy and the theories of desire merge and interweave. In this space, which undergoes constant renewal, literature is understood to be an intellectual and emotive experience, and an irreplaceable source of knowledge. Literary texts are studied as dynamic objects that are able to cross the borders of the era in which they were produced and enter the “great time” (as Bakhtin called it). However, a text can only expand, like the Japanese flowers that Proust spoke about at the beginning of the Recherche, if it is immersed in the water of good interpretations. And good interpretations are not infinite as Derrida and the followers of reception theory believed. Only doxa is infinite.Literature is a way of thinking. It offers the opportunity for a complex mental experience that no algorithm could ever describe or envisage. By creating characters with flexible identities, literature describes the human condition from the viewpoint of non-coincidence with oneself. It addresses all individuals inviting them to understand their higher possibilities.Yet these possibilities, the investigation of which is where the very vocation of literature lies, have always encountered enormous obstacles. The difficulty in understanding and analyzing those virtually expanding multilateral objects that are literary texts has caused most scholars to limit themselves to reductive and peripheral investigations. This type of research should be called contextualism. It has presented itself in different versions: the history of literature in the nineteenth century and the first half of the twentieth century, cultural studies (in other words the anti-theory) in the last few decades; but also in the form of an unlimited intertextualism (Derrida), far removed from any social-historic interest. However, all types of contextualism share a common attitude: they deny the individuality of the text, they ignore (or fear) the “labyrinth of linkages” (Tolstoy) that form it, its complexity and its beauty. Therefore, they take refuge in the contexts: the nation, the class, the race, the gender, the ideology, etc. or in the set of texts by the same author or by other authors.The inability to analyze and interpret literature has caused enormous damage. Contextualism destroys literature. These considerations are addressed not only to professors, but also to students in the hope that this damage is not (or will not become) irreversible. We can no longer postpone the rebellion against contextualism and the University requires innovation. The conceptually and methodologically reactionary studies must be fought, even when they masquerade as good intentions and try to hide their intellectual poverty behind stereotypes of ideology.
Keywords: Literary Theory; Interpretation; Identity; Flexibility; Cultural Studies